WORKSHOP PELATIHAN VISUAL ARSITEKTUR HERITAGE BERBASIS VISUAL ETHNOGRAPHY DAN ENGLISH HERITAGE INTERPRETATION - Alexander Adrian Saragi; Margaret Stevani; Fitri Rahmawati Nasution; Nurfaizah Marwan; Mentari Septanya Sitorus (Jurnal Pengabdian Masyarakat Sabangka, 2026)
The workshop on heritage architectural visualization, based on visual ethnography and English heritage interpretation, aimed to develop students’ technical, analytical, and communicative competencies in understanding and interpreting historical buildings. The methods employed included analytical sketching, field observation grounded in visual ethnography, and translating heritage interpretations into English. An interdisciplinary approach involved architecture lecturers from UNM and USU, along with English education lecturers from Universitas Pembinaan Masyarak at Indonesia, enabling the integration of visual design skills, historical understanding, and bilingual communication. Results sho wed significant improvements in perspective accuracy, proportion, material texture, and the ability to read structural and symbolic values of buildings. Students were also able to produce interpretative narratives in English to support professional heritage knowledge dissemination. This model proves effective as a sustaina ble collabor ative learning strategy, combining technical skills, academic reflect ion, & social awareness within an integrated educational framework